PENINGKATAN SELF-EFFICACY DIGITAL SISWA SEKOLAH DASAR MELALUI PELATIHAN DESAIN MENGGUNAKAN CANVA - Nurul S A Saifuddin; Bonar Hutapea (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
ABSTRACT The rapid advancement of digital technology has not been fully accompanied by elementary school students' ability to utilize digital tools productively and creatively. This condition was also observed among sixth-grade students at SD Negeri 01 Ciherang, Cianjur Regency, who demonstrated relatively low levels of digital self-efficacy in using digital devices and applications. This community service program aimed to enhance students' digital self-efficacy through graphic design training using the Canva application. The program was implemented in the form of a workshop and hands-on practice conducted over two face-to-face sessions, consisting of a training session and an evaluation session, involving 14 sixth-grade students. Evaluation was carried out using a validated Likert-scale digital self-efficacy questionnaire administered before and after the training. The data were analyzed using a paired-samples t-test. The results revealed a significant improvement in students' digital self-efficacy, with the mean score increasing from 22.14 in the pre-test to 24.64 in the post-test (t(13) = −4.700, p < 0.001). This improvement indicates increased confidence among students in operating digital devices, utilizing the Canva application, and independently creating digital graphic designs. These findings suggest that Canva-based training is an effective and practical intervention for strengthening digital self-efficacy among elementary school students. Furthermore, this program may serve as an alternative strategy for supporting the implementation of digital literacy initiatives in elementary schools. ABSTRAK Perkembangan teknologi digital belum sepenuhnya diikuti oleh kemampuan siswa sekolah dasar dalam memanfaatkan teknologi secara produktif dan kreatif. Kondisi tersebut juga ditemukan pada siswa kelas VI SD Negeri 01 Ciherang, Kabupaten Cianjur, yang menunjukkan tingkat self-efficacy digital relatif rendah dalam penggunaan perangkat dan aplikasi digital. Program pengabdian kepada masyarakat ini bertujuan meningkatkan self-efficacy digital siswa melalui pelatihan desain grafis berbasis aplikasi Canva. Kegiatan dilaksanakan dalam bentuk workshop dan praktik langsung yang diselenggarakan melalui dua pertemuan tatap muka, yaitu sesi pelatihan dan sesi evaluasi, dengan melibatkan 14 siswa kelas VI. Evaluasi dilakukan menggunakan angket self-efficacy digital berskala Likert yang diberikan sebelum dan sesudah pelatihan. Data dianalisis menggunakan uji Paired Sample t-Test. Hasil analisis menunjukkan adanya peningkatan self-efficacy digital yang signifikan, dengan rerata skor meningkat dari 22,14 pada pre-test menjadi 24,64 pada post-test (t(13) = −4,700; p < 0,001). Peningkatan tersebut mengindikasikan bertambahnya keyakinan siswa dalam mengoperasikan perangkat digital, memanfaatkan aplikasi Canva, serta menghasilkan karya desain secara lebih mandiri. Temuan ini menunjukkan bahwa pelatihan berbasis Canva merupakan alternatif intervensi yang efektif dan mudah diimplementasikan untuk mendukung penguatan self-efficacy digital siswa sekolah dasar. Kegiatan ini juga dapat menjadi salah satu strategi dalam mendukung pelaksanaan program literasi digital di lingkungan sekolah dasar.